2020
DOI: 10.1093/jhps/hnaa035
|View full text |Cite
|
Sign up to set email alerts
|

The effects of venting and capsulotomy on traction force and hip distraction in hip arthroscopy

Abstract: This study evaluated the effects of venting and capsulotomy on the ratio of normalized distraction distance to traction force, correlating this trend with patient demographic factors. A ratio was chosen to capture the total effect of each intervention on the hip joint. During primary hip arthroscopy, continuous traction force was recorded, and fluoroscopic images were acquired to measure joint distraction before and after the application of traction, venting and interportal capsulotomy. Distraction–traction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Several in vivo and cadaveric studies have shown that distension of the joint with air or fluid led to a breakage of the vacuum seal between the head and socket, resulting in subsequent improvement of distraction and reduction of the traction force. 3,5,16,17 Byrd et al 3 demonstrated that the distance between the superior weightbearing portion of the acetabulum and the corresponding femoral head (similar to the lateral gap in the current study) significantly increased by a mean of 22% via the addition of fluid distension to pure traction. Dienst et al 5 showed that the distraction distance of the lateral gap after a combination of air distension and traction was 1.45 to 3.07 times greater than that after traction alone in a cadaveric study.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Several in vivo and cadaveric studies have shown that distension of the joint with air or fluid led to a breakage of the vacuum seal between the head and socket, resulting in subsequent improvement of distraction and reduction of the traction force. 3,5,16,17 Byrd et al 3 demonstrated that the distance between the superior weightbearing portion of the acetabulum and the corresponding femoral head (similar to the lateral gap in the current study) significantly increased by a mean of 22% via the addition of fluid distension to pure traction. Dienst et al 5 showed that the distraction distance of the lateral gap after a combination of air distension and traction was 1.45 to 3.07 times greater than that after traction alone in a cadaveric study.…”
Section: Discussionsupporting
confidence: 74%
“…Another cause leading to the increase of distraction between the preoperative unsterile traction test and the end of arthroscopy is likely the physiologic creep of the soft tissues. This was confirmed by O'Neill et al, 16 who showed that distraction increased over time after application of traction. These findings provide some useful information for hip arthroscopy.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We must translate the bench to the bedside. Surgeons are finally starting to do this: O'Neill et al, 7,8 in 2 separate publications using a proprietary postless hip distraction system, have not only measured the strength of the seal, they have also provided recommendations for decreasing force of distraction. Personally, in my prospective database, I quantitatively measure and record several aspects of the seal and its breakage: after an air arthrogram, the force (Newtons; pounds of force) required to sufficiently distract the hip; the degrees of Trendelenburg of the bed; and the amount of femoral head distraction (millimeters).…”
Section: See Related Article On Page 352mentioning
confidence: 99%